National Unification and Economic Development in Vietnam - Beresford, Melanie. author. aut Link
XVI, 296 p.
Keywords: This study explains the economic upheavals experienced by Vietnam since the end of the War in terms of historical developments, especially the legacy of separation of North and South from 1954 to the 1975 Communist victory and traces aspects of the divided economies which have been of significance.